The way to a man's heart is through his stomach? A unique case report of transient constrictive pericarditis secondary to infarction of herniated omentum following bariatric surgery. Issue 6 (18th May 2022) - Singh, Suhasini; Rowe, M.; Hopkins, G.; Dahiya, A.
Abstract: Background: Intrapericardial diaphragmatic hernias are a rare form of diaphragmatic hernia. The presentation is usually acute due to trauma or from iatrogenic causes. In some instances however, these patients can present years later. We describe an unusual case of transient constrictive pericarditis associated with herniation of omentum through a diaphgragmatic hernia extending into the pericardial space, which infarcted following recent bariatric surgery. A multi-disciplinary approach was required with surgical correction of the diaphragmatic defect and removal of omentum from the pericardial space. Case summary: A 38-year-old gentleman with a history of a remote abdominal stab wound and recent laparoscopic gastric sleeve procedure presented with sharp central chest pain radiating to the shoulder. Chest imaging [echocardiography, computed tomography (CT), and cardiac magnetic resonance imaging (MRI)] revealed the presence of an intrapericardial diaphragmatic hernia and herniation of devascularized omentum into the pericardial space. Surgery was undertaken to remove the pericardial omentum. Echocardiography and cardiac MRI revealed changes of pericardial constriction which resolved with anti-inflammatories. Discussion: A multi-disciplinary approach was required in this case with surgical correction of the diaphragmatic defect and removal of omentum from the pericardial space. Multi-modal imaging proved essential in the diagnosis of this rare condition, aiding in timely diagnosis, ongoing management decisions, and for assessing therapeutic response.